2018
DOI: 10.3390/su10114066
|View full text |Cite
|
Sign up to set email alerts
|

Land-Use Spatio-Temporal Change and Its Driving Factors in an Artificial Forest Area in Southwest China

Abstract: Understanding the driving factors of land-use spatio-temporal change is important for the guidance of rational land-use management. Based on land-use data, household surveys and social economic data in 2000, 2005, 2010, and 2015, this study adopted the Binary Logistic Regression Model (BLRM) to analyze the driving factors of land-use spatio-temporal change in a large artificial forest area in the Ximeng County, Yunnan province, in Southwest China. Seventeen factors were used to reflect the socio-economic and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…Afforestation and economic tree plantation is another major carbon sequestration section in the mountain areas of west China [19] . In the recent decade, citrus planting has been rapidly developed in the TGR areas as local governments promoted economic development through the citrus industry.…”
Section: Assessment Of Carbon Footprintmentioning
confidence: 99%
“…Afforestation and economic tree plantation is another major carbon sequestration section in the mountain areas of west China [19] . In the recent decade, citrus planting has been rapidly developed in the TGR areas as local governments promoted economic development through the citrus industry.…”
Section: Assessment Of Carbon Footprintmentioning
confidence: 99%
“…Eker and Coban believed that roads in forest areas have many influences on landscapes, and their influence on the spatial structure of the forest landscape is significant [80]. Zhao et al studied artificial forest areas in Ximeng County in Yunnan province and found that accessibility plays a vital role in affecting land-use changes [81]. McGarigal et al investigated landscape changes affected by road construction and logging activity in the southern part of the North American Rockies.…”
Section: Research Studies On Rural Areas Focus On Farmingmentioning
confidence: 99%
“…The relationship means that closer these distances to the rice land area will increase the probability of rice land to change. It is a plausible relationship because urbanization growth is in line with the existence of road [53] and with the distance to the district capital/provincial capital. This table also indicates the probability of rice land change will increase by a factor of 0.99 for every 2696 m, 2321 m and 13,609 m of distance to the road, to the district capital and to the provincial capital, respectively.…”
Section: Factors Affecting Rice Land Changementioning
confidence: 99%